Perbandingan Ketuntasan Perawatan Klien Perilaku Kekerasan antara yang Menerima Komunikasi Terapeutik Perawat dan Pekerja Sosial (Sebuah Studi di UPT Rehabilitasi Sosial Eks Psikotik Pasuruan) - Tutu April Ariani (Journal of Ners and Midwifery, 2016)
Mental health is the emotional and sosial maturity of a person which is accompanied by a compatibility with himself and his surroundings. One of the deviant behavior of clients with mental disorders are violent behavior. The management of violent behavior can be done with therapeutic communication. The right therapeutic communication can be used to reduce the level of violent behavior. This study aimed to determine comparison completeness of client care with violent behavior who receive therapeutic communication between the nurses and sosial workers. Methods: The research design used in this research was the kind of research the comparative analysis with cross sectional approach. The sample in this research consisted of 16 clients violent behavior, 3 nurses, and 7sosial workers in UPT RSEP Pasuruan. The Sampling technique in this research was purposive sampling. The data analysis used Chi-Square test. Results: Based on the research result client violent behavior who receive therapeutic communication nurses with complete catagory were 3 people (18,8%), and not complete category were 5 people (31,3%). While the violent behavior of respondents who receive therapeutic communication with sosial workers complete catagory were 5 people (31,3%), and not complete catagory were 3 people (18,8%). Chi-Square test result in comparison completeness client care violent behavior who receive therapeutic communication between the nurses and sosial workers, the p value = 0,317 more than the tariff of significance (0,05). Conclusion: It was concluded that there was no difference in complete treatment of violent behavior between nurses and sosial workers in UPT RSEP Pasuruan